Say good-bye, Cy, to the Shores of Representation: Towards an Abstract Romanticism (Konturen, 2014)
This essay is concerned with the ways in which the works of Cy Twombly, especially those paintings that refer to and draw their impetus from the poetry of Shelley and Keats, elaborate an impulse towards abstraction already latent in Romanticism itself.